Private education supply in disadvantaged areas of the City of Buenos Aires and 'low-fee private schooling': Comparisons, contexts and implications - Mauro Carlos Moschetti (Arizona State University, 2015)
Recent studies have revealed an increase in the enrollment of students coming from vulnerable social sectors in private primary schools in the City of Buenos Aires. To date, the phenomenon of 'private education for the poor' has been principally studied in Asian and African countries, where the deficit of state educational supply has given rise to a multiplicity of private education undertakings of diverse nature. Using official statistical data, this article explores and describes the structure of private education supply in areas of low socioeconomic status in Buenos Aires and assesses the extent to which the category of low-fee private school (LFPS) contributes to understanding this phenomenon. Our analysis reveals a great heterogeneity in this sector of private education in Buenos Aires with regard to financing structures, monthly fees, and the legal forms in which schools operate. We also find the presence of a significant religious component. We suggest the possibility that private provision has helped to mitigate coverage imbalances at a 'micro-local' level in some of the studied areas. Our comparative approach evidences that the notion of LFPS provides a more normative than descriptive view, limiting the perception of a phenomenon that is actually much broader, multifaceted and dynamic.